Interleukin-6 trans signalling enhances photodynamic therapy by modulating cell cycling - Wei, L-H; Baumann, H; Tracy, E; Wang, Y; Hutson, A; Rose-John, S; Henderson, B W (British journal of cancer, 2007)
Photodynamic therapy (PDT) of solid tumours causes tissue damage that elicits local and systemic inflammation with major involvement of interleukin-6 (IL-6). We have previously reported that PDT-treated cells lose responsiveness to IL-6 cytokines. Therefore, it is unclear whether PDT surviving tumour cells are subject to regulation by IL-6 and whether this regulation could contribute to tumour control by PDT. We demonstrate in epithelial tumour cells that while the action of IL-6 cytokines through their membrane receptors is attenuated, regulation by IL-6 via trans-signalling is established. Soluble interleukin-6 receptor- α (IL-6R α ) (sIL-6R α ) and IL-6 were released by leucocytes in the presence of conditioned medium from PDT-treated tumour cells. Cells that had lost their membrane receptor IL-6R α due to PDT responded to treatment with the IL-6R–IL-6 complex (Hyper-IL-6) with activation of signal transducers and activator of transcription (STAT3) and ERK. Photodynamic therapy-treated cells, which were maintained during post-PDT recovery in presence of IL-6 or Hyper-IL-6, showed an enhanced suppression of proliferation. Cytokine-dependent inhibition of proliferation correlated with a decrease in cyclin E, CDK2 and Cdc25A, and enhancement of p27kip1 and hypophosphorylated Rb. The IL-6 trans-signalling-mediated attenuation of cell proliferation was also effective in vivo detectable by an improved Colon26 tumour cure by PDT combined with Hyper-IL-6 treatment. Prevention of IL-6 trans-signalling using soluble gp130 reduced curability. The data suggest that the post-PDT tumour milieu contains the necessary components to establish effective IL-6 trans-signalling, thus providing a means for more effective tumour control.